Angular Momentum of the Earth System - Jialin Lin (PANGAEA, 2019)
Angular momentum of the Earth system is calculated for the past 139 years (1880-2018) including contributions from the atmosphere, ocean and solid Earth. The global atmospheric angular momentum is calculated using five atmospheric reanalyses including NCEP, JRA-55, ERA-Interim, CFSR, and NOAA 20Cv2. The global oceanic angular momentum is calculated using five ocean reanalyses forced by the above atmospheric analyses including GECCO2, SODA3, ORAS5, CFSR, and SODA2.4.1. The angular momentum of solid Earth is derived from the length of the day measurements. The atmospheric angular momentum and solid Earth angular momentum are associated with global climate variability such as the El Nino/Southern Oscillation and Madden-Julian Oscillation, while the total angular momentum of the Earth system is related to inner core wobble and tidal gravitational forcing. The datasets have been used by Lin and Qian (2019) in studying lunar tidal forcing of ocean waves and the El Nino/Southern Oscillation.
Supplement to: Lin, Jialin; Qian, Taotao (2019): Switch Between El Nino and La Nina is Caused by Subsurface Ocean Waves Likely Driven by Lunar Tidal Forcing. Scientific Reports, 9(1), 13106, https://doi.org/10.1038/s41598-019-49678-w